The poison diary of 1996 part - III - Abd Razak, Dzulkifli (1997)
TOWARDS THE YEAR END, CONCERN about food poisoning mounted after a number of such cases were reported, both locally and globally. So too was the increasing concern about the problem of drug abuse. For Malaysia, in particular, the announcement that our fight against drug abuse had come to nought was a terrible blow, given the emerging problem of "ecstasy." Overall, it was a sad way to end the year. September Concern about food poisoning continued in the month of September. Japan's Health and Welfare Ministry were still at a loss as to the source of food contaminated with E. coli bacillus 0157, which left about 10,000 people sick nationwide and about 200 hospitalised. At the same time, the mayor of Sakai, the city most badly bit by the epidemic said he would take a 40% paycut for six months beginning October as he felt responsible for the epidemic.